The Precise Definition of the Payload Tube Furnaces for Units of Primary Oil Refining - Ulyev, L. M.; Kapustenko, P. O.; Melnykovskaya, L. A.; Nechyporenko, D. D. (The Italian Association of Chemical Engineering, 2013)
The article considers the primary oil refining unit AVDU A12/2 in the mode without vacuum unit. In this paper carried out extraction of data on process flows and equipment, tabulated streaming data. It is performed modelling of primary oil refining unit in the software package Unisim Design to refine the data. It was determined the potential energy savings through the using methods of the pinch analysis, done the project of reconstruction of AVDU A12/2 with the modelling in program Unisim Design to confirm the performance of the project. The amount of heat loss in the heat exchange equipment and pipes was calculated, have developed a method for the accurate determination of the payload tube furnaces.